2018
DOI: 10.4103/jpn.jpn_9_18
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical implications of osteogenesis imperfecta in a child after fall: Case illustration

Abstract: Osteogenesis imperfecta (OI) is a group of hereditary genetic pathologies of connective tissue, which is characterized by bone fragility and fractures. It is classified into types I, II, III, IV, V, and VI. The disorder is caused by an autosomal-dominant mutation in one of the two genes that encode the alpha chains of type I collagen, COL1A1 and COL1A2. Several central nervous system abnormalities have been described in children with OI, however, it has been through various case reports. The neurological abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Neuroimaging studies with MRI are reported to be substantial for several neurological implications that children with OI can present. [20][21][22][23] Titanium alloy that is used to manufacture the rod is safe for MRI examination with minimum artifacts. Another significant benefit with the titanium alloy telescopic rod is of the low cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies with MRI are reported to be substantial for several neurological implications that children with OI can present. [20][21][22][23] Titanium alloy that is used to manufacture the rod is safe for MRI examination with minimum artifacts. Another significant benefit with the titanium alloy telescopic rod is of the low cost.…”
Section: Discussionmentioning
confidence: 99%
“…6,14,15,19 Furthermore, the presence of stainlesssteel telescopic constructs (e.g., Fassier-Duval rod) in children with osteogenesis imperfecta raising concerns for magnetic resonance https://doi.org/10.1016/j.jor.2020.05.017 imaging (MRI) study is one more disadvantage. [20][21][22][23] Since February 2018, we have used a telescopic rod made of titanium alloy in combination with minimal external fixation. In literature, the combination of telescopic flexible intramedullary nailing with an external fixator in patients with osteogenesis imperfecta or other severe underlying bone pathology demonstrated advantages of stability, early weight-bearing and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%